Exploring novel phase of tin sulfide for photon/energy harvesting materials. (15th July 2018) - Rehman, Sajid Ur; Butt, Faheem K.; Ul Haq, Bakhtiar; AlFaify, Salem; Khan, Waheed S.; Li, Chuanbo
Graphical abstract: Highlights: First ever ab initio studies on cubic tin sulfide (π-SnS). The optical, elastic and anisotropic properties are presented. 2D & 3D surface visualization suggest that π-SnS is elastically anisotropic. π-SnS could be suitable candidate for optoelectronic, thermoelectric. Abstract: Recently discovered novel π-SnS (cubic phase) has gained much attention due to suitable nature for several optoelectronic devices and thermoelectric applications. Local density approximation (LDA) and generalized gradient approximation (GGA) with ultra-soft pseudo-potential (UPP) technique within density functional theory (DFT) are used to study the structural, electronic, optical, and elastic properties of π-SnS. The structural properties show good consistency with previous results. The band structure study shows that its nature is indirect with bandgap 1.073/1.37 eV (LDA/GGA). The calculated elastic constants satisfy the Born stability criteria which are determined for the first time as per our knowledge. On the basis of Voigt-Reuss-Hill approximation, bulk modulus, shear modulus, Young's modulus, Poisson's ratio, Lame's coefficients, average sound velocity and Debye temperature are determined. In LDA/GGA the value of Bulk modulus is estimated 55.32/20.98 GPa, which is in good agreement to that calculated with Birch-Murnaghan equation of state (EOS). The 2D and 3D surface visualization of bulk, shear and Young's moduli suggest that π-SnS is elastically anisotropic. In LDA/GGA the value of Debye temperature (θD ) is estimated as 361.01/299.39 K. The thermal conductivity of π-SnS could be high due to high Debye temperature (θD ) relative to α-SnS (θD ∼ 270 K). Additionally, for the first time transversal and longitudinal wave velocities in [1 0 0], [1 1 0] and [1 1 1] directions are calculated. In the view of present studies π-SnS could be suitable candidate for exploitation in optoelectronic, thermoelectric and energy storage devices.